Ability of photocurable gelatin to prevent stricture recurrence after urethral dilation in rabbits. (18th October 2021) - Ojima, Kenichiro; Kushibiki, Toshihiro; Mayumi, Yoshine; Miyai, Kosuke; Shinchi, Masayuki; Hirano, Yusuke; Azuma, Ryuichi; Ito, Keiichi; Ishihara, Miya; Horiguchi, Akio
Abstract : Objectives: To evaluate the ability of photocurable gelatin to prevent stricture recurrence after urethral dilation in a rabbit urethral stricture model. Methods: We created urethral strictures in the bulbar urethras of 10 male Japanese white rabbits using electrocoagulation. After 1 month, the rabbits were randomly divided into Group A ( n = 5; urethral stricture dilation and the local application of photocurable gelatin using a ruthenium photoinitiator and irradiation with a light‐emitting diode light [λ = 455 nm, 50 mW/cm 2 ] for 1 min) and Group B ( n = 5; dilation only). Urethral stricture status was evaluated 1–2 months later by retrograde urethrography and urethroscopy. The lumen ratio (urethral width at the stricture site to the normal urethral width on retrograde urethrography) was calculated. Urethral patency was considered to be improved when the urethral lumen could accommodate a 10‐Fr urethroscope without resistance. Urethral specimens were harvested for histopathological examination. Results: The mean lumen ratio did not differ significantly between Groups A and B before dilation (25.8% vs 23.4%; P = 0.40), but differed significantly after dilation (65.5% vs 27.3%, respectively; P = 0.03). Urethral patency improved in all rabbits in Group A (100%) versus one rabbit in Group B (20%; P = 0.02). The mean circumference of the regenerated urethral epithelium at the stricture site was larger in Group A than in Group B (14 mm vs 6.6 mm; P = 0.06). Conclusions: Photocurable gelatin can reduce urethral stricture recurrence after dilation in a rabbit model.